2016
DOI: 10.1097/01.asw.0000480458.60005.34
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Pressure Therapy to Reduce the Risk of Wound Infection Following Diverting Loop Ileostomy Reversal

Abstract: The negative-pressure Prevena System was safe and easy to use and may prevent SSIs in dirty wounds, such as those from ileostomy closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 21 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Data from the literature vary tremendously in SSSI rates when using iNPWT. Cantero et al reported a SSSI rate of 0% after reversal of double loop ileostomy . Nevertheless, in this study iNPWT was applied for 7 days to the wound and a different wound closure technique was performed (staples).…”
Section: Discussionmentioning
confidence: 85%
“…Data from the literature vary tremendously in SSSI rates when using iNPWT. Cantero et al reported a SSSI rate of 0% after reversal of double loop ileostomy . Nevertheless, in this study iNPWT was applied for 7 days to the wound and a different wound closure technique was performed (staples).…”
Section: Discussionmentioning
confidence: 85%
“…However, the study did not compare the wound-healing period between the two groups. Two additional studies evaluated the application of NPWT to ileostomy closure sites and demonstrated the efficacy of NPWT in reducing the SSI rate [17, 18]. However, these previous studies focused on patients with primary linear closure of stoma wounds and did not evaluate the wound-healing period.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there have been no studies demonstrating the use of prophylactic NPWT after Whipple procedures, a few smaller studies have shown benefit of prophylactic NPWT use after orthopedic, colorectal, vascular, plastics, cardiothoracic, and trauma procedures. 3,4 Methodology With Institutional Review Board approval, we retrospectively examined consecutive patients from January 2014 to July 2016 who met the criteria of completing a Whipple procedure with full primary incision closure performed by a single surgeon at a single institution. Standard recommendations for SSI reduction were used in all cases (wound protector, glove change prior to closure, perioperative antibiotics).…”
mentioning
confidence: 99%